PROBLEM „PONADCZASOWOŚCI” ZASAD PRAWA RZYMSKIEGO. UWAGI W DYSKUSJI O „NOWEJ EUROPEJSKIEJ KULTURZE PRAWNEJ” - Dajczak, Wojciech (Zeszyty Prawnicze, 2017)
The Issue of „ Timeless” Nature of the Rules of the Roman Law. Remarks in the Discussion on „the New European Legal Culture” Summary With in the scope of a discussion on the new European private law opinions regarding the need for a realist revolution are formulated, which would aim at conquering its formal systematics and dogmatic character. From this perspective the references to Roman law are criticised in relations to establishing an extranational private law. They are called neo-pandectism and qualified as dogmatic trends in the European private law. Referring to that discussion I ask in the article whether the realistic thinking about law allows to ignore the durable rules originating from the Roman law. While presenting the characteristics of the realism of the Roman jurists above all I indicated the conviction of the existence of rules that were primary to law, which should be taken into account in the lawyers’ evaluations. I voiced an opinion that seeing the durability of some of the Roman rationes decidendi there is no point in discussing the references to the Roman tradition in the context of the dispute between the realism and formalism but as an element of a dispute regarding the issue what the realistic thinking about law is. On the basis of the used sources I formulated a conclusion that the realistic thinking about law does not allow to ignore the reflection on the durability of the rules originating from the Roman law when we assume that the basis of the reasonable actions of the law-making bodies as well as the bodies which apply the law should be requirements of practical reasonableness, which have a primary nature to law